Features of the interaction of investigation and operational units of internal affairs department during the investigation of crimes in the sphere of public procurement - Часова, Т. О. (Theory and practice of jurisprudence, 2016)
Problem setting. Crimes in public procurement are characterized by a large great variety of methods of committing, every year the criminals improved the process of it masking. And that requires from police of commitment an effective coordinated measures which should combine a view that caused one of the main objectives of the police - protecting property from criminal attacks. From the community, recently more and more attention is paid to combating with crimes and other violations of legislation in the sphere of public procurement. However, imperfection of legislation and insufficient study of these problems are required a careful attention and study by scientists. Recent research and publications analysis. The issues of cooperation between investigators and operational units of internal affairs department during the investigation of crimes in the sphere of public procurement are studied by such scientists such as: A. Volobuev, V. Hlaskov, V. Daragan, M. Kazarenko, O. Kupriyanov, A. Mezhyvoy, S. Obshalov, V. Pyvovarov, D. Pysmenyy, V. Pcholkin, L. Skalozub, I. Skulyak, V. Fedchenko, N. Chernyak, L. Scherbyna et al. However, the issue features the interaction of investigation and operational units of internal affairs department during the investigation of crimes in the sphere of public procurement has not yet received a proper generalization of the scientific achievements of scientists. The object of the article. The purpose of the article is to study the characteristics of interaction between investigators and units of internal affairs department during the investigation of crimes in the sphere of public procurement. Article main body. In the process of combating with crimes in the sphere of public procurement the close cooperation between the investigative and operational units of the police are required. During such cooperation the issues of both procedural and operational and investigation character are solved. A special place in the interaction of investigative and operational units of the police while combating crime in public procurement takes teamwork during the investigation of such offenses. The most common forms of interaction between investigators and the units of the police during the investigation of crime in public procurement are: mutual consultation; joint analysis and evaluation of the information and materials of the criminal proceedings; development the plan of investigative actions; joint participation in the investigative action. Important role in the rapid investigation of crime in the sphere of public procurement the correct segregation of duties between investigators and staff in the units of the police at the time of appointment and conduct separate investigation action is played. Conclusions of the research. Based on the above, it can be concluded that the key to successful interaction between investigators and the units of the police during the investigation of crime in public procurement is an optimal allocation of responsibilities among its members, coordinated planning investigative operational actions and measures search ongoing mutual exchange of information and the timely introduction of adjustments to the work plan for the investigation of criminal proceedings.